Policy deployment in CTRM Aero Composites / Aimi Hamzah - Hamzah, Aimi (Faculty of Business and Management, 2011)
Policy Deployment in CTRM Aero Composites is a new thing to the company. This policy helps inter department to align and communicate towards objective and goals of the company. Basically this policy is introduced by their customer as to fulfill the requirement from their customer that is “Goodrich”. After some research being done the policy have been adapted and make some changes to the process in this policy to make it suitable with working culture in CTRM itself. This research designed because to know how effectives the policy deployment are. In this study also some research been done to measure the best practice that CTRM AC Should adapt to align and make the whole company achieved towards the same goals and objectives. The issue that could be raised is, since in CTRM there is many policies been applied, some measures been applied to know either the policy been deployed effectively in CTRM AC.